Peningkatan Hasil Belajar Menulis Teks Deskripsi Melalui Culturally Responsive Teaching (CRT) Pada Siswa Kelas VII SMPN 48 Makassar - Safebri, Hikmah; Usman, Usman; Nurfaidah, Nurfaidah (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the application of Culturally Responsive Teaching (CRT) approach in improving the writing skills of description text of seventh grade students of SMP Negeri 48 Makassar. The method used was Classroom Action Research which was conducted in two cycles. The research subjects consisted of 34 students of class VII SMP Negeri 48 Makassar. Data collection techniques included observation, writing tests, interviews with students, and documentation. The instruments used consisted of tests to measure descriptive text writing skills and non-tests in the form of observation sheets and interviews aimed at analysing the learning process. The data collected was analysed using qualitative and quantitative descriptive methods. The results showed a significant improvement in students' descriptive writing skills from the first cycle to the second cycle. In the first cycle, the students' completion rate only reached 38% with an average score of 71. Many students had difficulty in describing objects in detail, using grammar appropriately, and composing texts according to the expected structure. However, in the second cycle, after the approach was improved and intensive guidance was given, the students' completion rate increased to 91% with an average score of 84. This improvement proves that the Culturally Responsive Teaching (CRT) approach is effective in improving students' description text writing skills.